Smoke but no fire: convicting the innocent of crimes that never happened - Henry, Jessica S. (University of California Press, 2020)
Introduction : phantom crimes -- Forensic error : misclassified murders and mislabeled crimes -- False accusations : when lies become courtroom truths -- Police : crossing "the thin blue line" -- Prosecutors : winning, at all costs -- Defense lawyers : drowning in cases -- Judges : tilting the scales of justice -- Misdemeanors : not minor matters -- Conclusion : clearing the smoke